2023
DOI: 10.1590/0103-8478cr20220636
|View full text |Cite
|
Sign up to set email alerts
|

Review: Biological, antioxidant and phytochemical activities of Musa spp.

Abstract: Banana (Musa spp.) is a food with high nutritional value. Studies about its compounds have increased considerably due to the antioxidant and biological activities of the fruit. Thus, this article synthesized and organized data related to the phytochemical constituents, as well as antioxidant and biological activities of Musa acuminata, Musa balbisiana and Musa paradisiaca, and evaluated the mutual influence and correlation of these activities. A bibliographic review was performed using the scientific databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…is also another edible fruit in the form of banana and plantain, which is highly nutritious and, more so, an erect perennial plant with enormous benefit [11]. Numerous research has demonstrated these advantages along with antioxidant qualities that include anticancer, antifungal, and antibacterial [12]. Their physiological traits on the life cycle, plant geometry, and their nature, which happens to be a part of plant breeding, provide means to bio-accumulate pollutants from the area.…”
Section: Introductionmentioning
confidence: 99%
“…is also another edible fruit in the form of banana and plantain, which is highly nutritious and, more so, an erect perennial plant with enormous benefit [11]. Numerous research has demonstrated these advantages along with antioxidant qualities that include anticancer, antifungal, and antibacterial [12]. Their physiological traits on the life cycle, plant geometry, and their nature, which happens to be a part of plant breeding, provide means to bio-accumulate pollutants from the area.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on MP plant have reviewed the presence of phytochemicals such as phenolic compounds, avonoids; and others including alkaloids, tannins and saponins (Onyenekwe et al, 2013;Gervásio and Batitucci 2023). Furthermore, a recent study has also proven that MP stem juice has the therapeutic ability to prevent seizures by positively in uencing the associated biochemical parameters such as GABA, glutamate, GABA-T and brain histology of the experimental rats (Ugwuoke et al, 2023).…”
Section: Introductionmentioning
confidence: 99%